An Exploration of First-Generation College Students' Career Development Beliefs and Experiences. (August 2015) - Tate, Kevin A.; Caperton, William; Kaiser, Dakota; Pruitt, Nathan T.; White, Heather; Hall, Eric
First-generation college students (FGCS) represent a large proportion of individuals seeking higher education in the United States; yet this population does not perform as well academically as, and persist to graduation at lower rates than, their peers who have more familial context for the college-going experience. Completing a college degree is clearly tied to employability and mental wellness, which makes FGCS's plight an important issue. Although there is a significant body of research about FGCS's academic performance and experiences, there is little research about this population's beliefs and experiences along their career path. Using an exploratory qualitative approach (Consensual Qualitative Research) and a well-researched model of career development (Social Cognitive Career Theory), we asked 15 FGCS about external influences on, and internal beliefs about, their career development process. Three major domains emerged from the data— external influences on the career development process, understanding of the career development process, and self-concept. These results provide a foundation for future research, as well as implications for practice with this population.